ARF4 acting upstream of LBD16 promotes adventitious root formation in peach - Jingjing Liu; Lingling Gao; Ruoxi Zhang; Anqi Gao; Zamith Kerubo Oginga; Beibei Zheng; Yuepeng Han (Horticultural Plant Journal)
Although class A auxin response factors (ARFs) are known to regulate adventitious root (AR) development through the canonical SCFTIR1-Aux/IAA-ARF signaling pathway, the regulatory role of class B ARFs in AR development remains largely unclear. Therefore, this research focused on the role of class B ARF transcription factors in peach (Prunus persica ‘Shengli’) adventitious root formation. Here, we report the role of a class B ARF gene PpARF4 in adventitious root formation in peach. Comparative transcriptome and qRT-PCR analyses showed that the transcription of PpARF4 was significantly up-regulated in auxin-treated stem explants. Y2H assay showed that PpARF4 had no interaction with PpIAAs (AUXIN/INDOLE ACETIC ACIDs). PpARF4 could bind the promoters of lateral root development gene PpLBD16 and auxin transport gene PpPIN1 to activate their transcription. Ectopic overexpression of PpARF4 and PpLBD16 in Arabidopsis promoted AR development. Additionally, PpARF4 could act as a negative regulator of flavone synthesis and thus prevent the explants from browning. The results not only provide novel insights into the functions of ARFs in regulating plant growth and development, but will also be useful for fulfilling asexual propagation by stem cuttings in peach.